2018
DOI: 10.1371/journal.pone.0200903
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-induced plant resistance against soybean cyst nematode via root exudation of phenolic acids and plant pathogen-related genes

Abstract: Soybean cyst nematode (SCN) is a severe soil borne disease. The control of this disease is still a worldwide problem in agriculture. In this study, we found that application of potassium (K) fertilizer could decrease the occurrence of SCN at two field sites. Furthermore, the application of K could suppress Heterodera glycines with the activation of Phenylalanine Ammonia Lyase (PAL) and Polyphenol Oxidase (PPO) expression via pot experiments in a greenhouse. The release of cinnamic, ferulic and salicylic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
0
22
0
2
Order By: Relevance
“…As already mentioned, phenolic acids are involved in plant growth, antioxidant defence, and plant/microbe interaction [ 56 , 57 ]. Indeed, these compounds can be secreted by roots and act as allelochemicals by suppressing the proliferation of pathogens [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…As already mentioned, phenolic acids are involved in plant growth, antioxidant defence, and plant/microbe interaction [ 56 , 57 ]. Indeed, these compounds can be secreted by roots and act as allelochemicals by suppressing the proliferation of pathogens [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that the irrigation mode can affect the yields and qualities of tomato because CI and DI systems cannot directly and precisely contact the rhizosphere zone; thus, it is easy to cause the fixation and loss of nutrients, which will reduce the uptake nutrients from the roots and increase the accumulation of dry matter and reduce the yields and qualities of the crop. Meanwhile, the macroelements of nitrogen (N), phosphorus (P) and potassium (K) play an important role in the yields and qualities of plants [23][24][25][26]. We found that the NPK contents of the plants were significantly higher in the NPI treatment than in the CI and DI treatments (Table 3), which indicates that the higher frequency of NPI over a long period can maintain consistent nutrient concentrations in the root zone, promote the development of the root system, enhance the photosynthetic rate and chlorophyll content to promote photosynthesis and nutrient uptake and accumulation and finally increase the crop yield and quality [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Pemupukan berperan dalam perlindungan tanaman karet secara tidak langsung yaitu menekan perkembangan patogen, melalui induksi kesehatan tanaman karet. Beberapa penelitian membahas mengenai peran nitrogen dan kalium telah dilakukan dalam usaha perlindungan tanaman melalui pemupukan (Veresoglou et al 2013;Wang et al 2013;Gao et al 2018).…”
Section: Penuruanan Intensitas Seranganunclassified